Susceptibility of five forest species to Coptotermes gestroi - Souza,José Hildefonso de (2009)
Termites are well known for their ability to damage wood and various types of wood-derived products. This study was performed in the municipality of Seropédica, Rio de Janeiro state, Brazil, with the objective of evaluating the susceptibility of the wood of five different forest species to the activity of the Asian subterranean termite, Coptotermes gestroi. Wood stakes from the following forest species were used as specimens: pine (Pinus sp., Pinaceae), Brazil nut (Bertholletia excelsa, Lecythidaceae), cabbage angelin (Andira inermis, Leguminosae-Papilionoideae), maçaranduba (Manilkara huberi, Sapotaceae) and pink ipê (Tabebuia avellanedae, Bignoniaceae). The stakes, with dimensions of 2 cm x 2 cm x 16 cm, were subjected to the activity of C. gestroi from September 2, 2006 to June 2, 2007. The experimental design consisted of randomized blocks with four replications in an 11 x 5 x 3 factorial arrangement. Twelve stakes of each of the five forest species were installed at each of eleven sites, totaling 660 stakes. Three evaluations were performed, at 90, 180 and 270 days after stake installation. The results indicated that the pine, Brazil nut and cabbage angelin stakes were more susceptible to C. gestroi attack, while the pink ipê and maçaranduba stakes suffered no significant damage from this termite. There was a significant negative correlation between the wood consumption rate and the wood density of the species studied. The woods most susceptible to C. gestroi attack presented moderate to low densities and therefore less resistance, as in the case of pine and cabbage angelin.